Effect of gamma irradiation on seedling parameters of amaranthus (Amaranthus cruentus) genotype IC-35540 - Harivendra; Prashant Kumar Rai; Vaidurya Pratap Sahi; Bazil Avinash Singh (Annals of Agricultural Research, 2024)
The present study was conducted to evaluate the effect of different doses of gamma irradiation on seedling parameters and nutritional values of Amaranthus genotype IC-35540 in the Notified State Seed Testing Laboratory of the Department of Genetics and Plant Breeding, Sam Higginbottom University of Agriculture, Technology, and Sciences, Prayagraj, Uttar Pradesh, BHARAT during July, 2023 to June, 2024 in complete randomized design alongwith four replications. The seeds of amaranthus genotype IC 35540 were treated with the ten treatments of gamma ray doses ranging from 5 kR to 50 kR (T1 to T10) alongwith control (T0). Key observations included seed germination percentage, germination energy, shoot and root length, seedling length, fresh and dry weight, vigour indices I and II, and nutritional components such as protein, carbohydrate, ash, moisture, iron, zinc, calcium, and magnesium. The findings revealed that lower doses of gamma irradiation, notably at 5 kR, markedly improved seedling parameters including germination percentage, germination energy, shoot and root length, seedling length, fresh and dry weight, and vigour indices. The 10 kR dose also had beneficial effects, though to a lesser degree. Higher doses, particularly 50 kR, had a negative impact on seedling growth, showing a dose-dependent decline in performance with increased gamma irradiation. The 5 kR treatment not only enhanced seedling parameters but also positively affected the nutritional and mineral composition of the plants. In summary, the 5 kR dose proved to be the most effective in enhancing both growth and nutritional quality in Amaranthus genotype IC-35540. These results indicate that careful dose optimization of gamma irradiation can be an effective strategy for advancing plant breeding and cultivation practices.